Quality Improvement Initiative to Reduce Admissions for Nephrotic Syndrome Relapse in Pediatric Patients - Charnaya, Olga; Ahn, Sun-Young (Frontiers in Pediatrics, 2019)
Introduction: Childhood nephrotic syndrome is frequently seen in pediatric nephrology practice and often requires patient hospitalization for management. Numerous complications of this disease can be managed in an outpatient setting if brought to the attention of the medical team in a timely manner. Outpatient management will reduce healthcare cost and improve patient safety. The goal of this quality improvement initiative was to reduce admissions for nephrotic syndrome relapse from 8 to less than 5 admissions at a single center in a 3-month period. Methods: Fish-bone analysis was used to determine barriers to early recognition of relapse and successful outpatient care. Patient education about the disease process was identified as the primary barrier. A standardized approach to patient education as well as educational materials were developed. Champions were identified within each stakeholder group to train and disseminate the new process. Admission counts were compared from 3 years prior to implementation to 2 years post-implementation. Clinic visits for nephrotic syndrome were tallied as a balancing measure. Patients were surveyed in the outpatient clinics about whether they had ever received the education as a process measure. Results: Admission counts were reduced and met goal for the first 3 quarters that were examined; however, the number of admissions went above target in the last quarter. Clinic visit numbers did not change over the study period. Process measure showed that 75-80% of families were provided with nephrotic syndrome education. Conclusion: A standardized approach to patient and family education about idiopathic nephrotic syndrome can reduce admissions for management of relapse. This will reduce healthcare expenditure as well as improve patient safety.